39.1: Invited Paper: Printed Inorganic Transistors Based on Transparent Oxides. Issue 1 (June 2015) - Subramanian, Vivek; Jang, Jaewon; Scheideler, William; Swisher, Sarah
Abstract : Transparent transistors based on inorganic oxides have received attention in recent years due to their high performance and excellent optical transparency. For large area and flexible display applications, the development of a printing‐based route to realize these devices is particularly interesting due to the potential for realization of a scalable and low‐cost manufacturing process. Here, we review our work on the development of printed transparent oxide transistors based on indium and tin oxides. We discuss the formulation of inks for printing of transparent conductors, semiconductors, and dielectrics, and show how these can be integrated using inkjet and gravure printing to realize high‐performance fully printed transparent oxide transistors.